Early modern Jewish civilization
1 online resource (vi, 462 pages)
Keywords: "This collection is an introductory historical survey and selective cultural analysis of the development, coalescence, and eventual waning of a diasporic civilization-that of the Jews of the early modern period (ca. 1391-1789) in Europe, the Ottoman Empire, and key nodes of the Iberian Empires in the Americas. Early Modern Jewish Civilization is essential reading for all students of Jewish history and civilization and early modern history more broadly"--